Translation as alchemy: the aesthetics of multilingualism in film - Şerban, Adriana (MonTi Monografías de Traducción e Interpretación, 2014)
The aim of this paper is to explore the aesthetics of multilingualism in film. We start with a discussion of translation strategy in several films and continue with two case studies based on Azur et Asmar (2006) by Michel Ocelot, on the one hand, and Nostalghia (1983) and Offret (1986) by Andrei Tarkovsky, on the other. Our analysis does not involve a comparison between the original dialogues or monologues and their translations into one or several languages, but, rather, it focuses on the role of translation in film making, considering it independently from any pre-existing oral or written texts. This will lead us to a number of reflections about the possibility and the limits of communication, about poetry and cinematography, and the role of language(s) and silence in film.